The Role of Civic Education in the Formation of National Identity and Awareness of the Indonesian Nation in the Era of Globalization - Bagus Maulana; Diana Marsela; Naya Uzzahra; Sri Wahyuningsih; Afandi Afandi (CV. Rayyan Dwi Bharata, 2023)
Citizenship education is education that includes nationality and citizenship and its relationship with the state and democracy. In the current era of globalization, education is one of the media that is very effectively used to form national identity and build awareness of the Indonesian people. Globalization can be characterized by openness between one country and another. The current rapid development of globalization causes humans to be required to have qualified competitiveness due to the rapid flow of information and technology so that as individuals, we must have and develop the potential of ourselves, groups and all levels of society. Citizenship education in shaping national identity and national awareness in the current era of globalization has its own conveniences and challenges for us. In-depth improvement regarding citizenship education must be realized again in its implementation considering that currently the development of globalization is so rapid.